Haste makes waste: Decision making in patients with restless legs syndrome with and without augmentation. - Beatrice Heim; Marie-Theres Pertl; Ambra Stefani; Margarete Delazer; Anna Heidbreder; Laura Zamarian; Elisabeth Brandauer; Klaus Seppi; Birgit Högl; Werner Poewe; Atbin Djamshidian (PLoS ONE, 2017)
OBJECTIVES:To investigate decision making in patients with primary restless legs syndrome (RLS) with and without augmentation treated with dopaminergic medication. METHODS:A total of 64 non-demented RLS patients treated with dopaminergic medication with and without augmentation were included in this study. We used an information sampling task to assess how much evidence participants gather before making a decision. Performance was compared to the results of 21 healthy controls. RESULTS:All patients with and without augmentation gathered less information than healthy controls before making a decision (p<0.001), but there was no difference between the two patient groups (p = 1.0). Furthermore, both patient groups made more irrational decisions (e.g. decisions against the evidence they had at the time) than healthy controls (p≤0.002). In addition, RLS patients with augmentation made significantly more irrational decisions than RLS patients without augmentation (p = 0.037) and controls (p<0.001). CONCLUSIONS:Our results show that RLS patients treated with dopaminergic drugs, regardless of having augmentation or not, jumped to conclusions and decided significantly more often against the evidence they had at the time of their decision. However, those with augmentation performed worse than all other groups and made more often irrational decisions, a phenomenon which is also common in patients with substance abuse or behavioural addictions. Thus, jumping to conclusions and deciding with a higher degree of uncertainty as well as irrational decision making is more common in RLS patients treated with dopaminergic medication particularly in those with augmentation.